2022
DOI: 10.12688/f1000research.108731.1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and prevention practice against dengue vectors among dengue patients and general people in Chattogram, Bangladesh

Abstract: Background: Due to the absence of an effective vaccine for dengue, community-led vector control strategy could be a sustainable approach for dengue prevention. Therefore, this study aimed to assess people’s knowledge of dengue vectors and the practice of preventive measures to avoid vector mosquitoes by means of a structured questionnaire. Methods: A telephone-based survey was conducted between July 2019 to December 2019 from confirmed dengue patients and general people without dengue fever living in Chattogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…14 Though there is variation in results among the previous studies, result of current study falls within the ranges reported in previous literature around the world about the level of knowledge on dengue ranging from approximately 2.3 to 62.0 percent. [15][16][17]20,21 Regarding to overall dengue prevention practices, the current study reported that only 38.1 percent of the respondents had good dengue preventive practices. Previous two studies from Nepal have suggested 21.2 percent 5 and 62.0 percent 15 of the respondents had good dengue preventive.…”
Section: Discussionmentioning
confidence: 96%
“…14 Though there is variation in results among the previous studies, result of current study falls within the ranges reported in previous literature around the world about the level of knowledge on dengue ranging from approximately 2.3 to 62.0 percent. [15][16][17]20,21 Regarding to overall dengue prevention practices, the current study reported that only 38.1 percent of the respondents had good dengue preventive practices. Previous two studies from Nepal have suggested 21.2 percent 5 and 62.0 percent 15 of the respondents had good dengue preventive.…”
Section: Discussionmentioning
confidence: 96%
“…The situation worsened in 2019, with over 100 thousand confirmed cases and 164 deaths due to dengue fever -an alarming 11-fold increase compared to the previous year. (Directorate General of Health Services (DGHS), 2020; Rafi et al, 2020) (Rahman, Mehejabin, & Rashid, 2022).…”
Section: Introductionmentioning
confidence: 99%